Verification of TRI3 Acetylation of Trichodermol to Trichodermin in the Plant Endophyte Trichoderma taxi - Chen, Haijiang; Mao, Lijuan; Zhao, Nan; Xia, Chenyang; Liu, Jian; Kubicek, Christian P.; Wu, Wenneng; Xu, Su; Zhang, Chulong (Frontiers in Microbiology, 2021)
Trichodermin, a trichothecene first isolated in Trichoderma species, is a sesquiterpenoid antibiotic that exhibits significant inhibitory activity to the growth of many pathogenic fungi such as Candida albicans, Rhizoctonia solani and Botrytis cinerea by inhibiting the peptidyl transferase involved in eukaryotic protein synthesis. Trichodermin has also been shown to selectively induce cell apoptosis in several cancer cell lines and thus can act as a potential lead compound for developing anti-cancer therapeutics. The biosynthetic pathway of trichodermin in Trichoderma has been identified and most of the involved genes have been functionally characterized. An exception is TRI3, which encodes a putative acetyltransferase. Here we report the identification of a gene cluster that contains seven genes expectedly involved in trichodermin biosynthesis (TRI3, TRI4, TRI6, TRI10, TRI11, TRI12 and TRI14) in the trichodermin-producing endophytic fungus Trichoderma taxi. As in Trichoderma brevicompactum, TRI5 is not included in the cluster. Functional analysis provides evidence that TRI3 acetylates trichodermol, the immediate precursor, to trichodermin. Disruption of the TRI3 gene eliminated the inhibition to R. solani by T. taxi culture filtrates, and significantly reduced the production of trichodermin but not of trichodermol. Both the inhibitory activity and the trichodermin production were restored when the native TRI3 gene was reintroduced into the disruption mutant. Furthermore, a His-tag-purified TRI3 protein, expressed in Escherichia coli, was able to convert trichodermol to trichodermin in the presence of acetyl-CoA. The disruption of TRI3 also resulted in lowered expression of both the upstream biosynthesis TRI genes and the regulator genes. Our data demonstrate that T. taxi TRI3 encodes an acetyltransferase that catalyzes the esterification of the C-4 oxygen atom on trichodermol and thus plays an essential role in trichodermin biosynthesis in this fungus.